Biologie des Stöckers in Nordsee und Nordostatlantik - Zimmermann, Christopher; Hammer, Cornelius (1999)
This paper summarises the current knowledge on horse mackerel (Trachurus trachurus) biology. The synopsis is mainly based on the report of a recently conducted EU funded workshop on horse mackerel age reading. A brief description of this workshop and of recent developments in sampling of German commercial horse mackerel catches is given. Johann Heinrich von Thünen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung = Information on Fishery research in 2010.